2014
DOI: 10.1016/j.ijid.2014.03.1340
|View full text |Cite
|
Sign up to set email alerts
|

Association of toll-like receptor 3 polymorphism with chronic hepatitis B

Abstract: Background: Previous studies in an experimental model of rabies showed neuronal process degeneration in association with severe clinical disease. Cultured adult rat dorsal root ganglion (DRG) neurons infected with CVS-11 strain of rabies virus (RABV) showed axonal swellings and immunostaining for 4-hydroxy-2-nonenal (4-HNE) indicating evidence of lipid peroxidation associated with oxidative stress and reduced axonal growth versus mock-infection. We have demonstrated that RABV induces alterations in a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, it might have a protective role in reducing the risk of a CHB infection. 100 Chihab et al reported the role of TLR9 SNPs in the anti-viral immune response. SNP of TLT9 (rs5743836; AA, AG to GG) and rs187084 (AA) studied in CHB patients, and a significant association between HBV progression and TLR9 polymorphism rs187084 (AA) was found 101 (Table 2).…”
Section: Hepatitis Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it might have a protective role in reducing the risk of a CHB infection. 100 Chihab et al reported the role of TLR9 SNPs in the anti-viral immune response. SNP of TLT9 (rs5743836; AA, AG to GG) and rs187084 (AA) studied in CHB patients, and a significant association between HBV progression and TLR9 polymorphism rs187084 (AA) was found 101 (Table 2).…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Another study reported that TLR3 SNP (1377CC and TT) increases a 2.4 fold higher risk of a CHB infection than (1377CT) polymorphism. Thus, it might have a protective role in reducing the risk of a CHB infection 100 . Chihab et al reported the role of TLR9 SNPs in the anti‐viral immune response.…”
Section: Viral Stismentioning
confidence: 99%